Tradisi Pernikahan Adat Jawa Kepenghuluan Kencana Kecamatan Balai Jaya Kabupaten Rokan Hilir - Wardiana, Irna; Widodo, Teguh (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research was conducted in Kepenghuluan Kencana, Balai Jaya Subdistrict, Rokan Hilir Regency which aims to find out the process of Javanese traditional marriage tradition in Kepenghuluan Kencana, the meaning contained in each procession of Javanese traditional marriage of Kepenghuluan Kencana, and the factors causing changes in the procession of Javanese traditional marriage of Kepenghuluan Kencana. In determining the research subject using criteria determined by the researcher with Purposive Technique. This research uses qualitative methods with data collection techniques through interviews and documentation. The results of the study prove that the first procession is a procession before the implementation event, this procession is in the form of proposals and offerings, installing tratag, and kenduri. The second is the procession of the wedding ceremony which includes the marriage contract, panggih manten (berbalang gantal, ngidak tigan, putaran talak bala, sinduran, sungkeman, kacar-kucur, sulangan). And finally the procession after the wedding is the ngunduh mantu event. The Javanese traditional wedding procession is not just an ordinary process, but there are expectations from the family and the closest people to live a good household life. The Javanese traditional wedding procession has changed in several stages of the procession held, but now the community prefers to hold events that are considered important. This is influenced by several factors such as lineage, contact with other cultures, and environmental factors.